Innovation development and the emergence of fast-growing companies in Russian regions - Alla Sorokina; V. Barinova (European Regional Science Association (ERSA), 2014)
In my presentation I would like to describe the results of a RANEPA team research project in which I am participating. The main object of presented research is factors that determine companies' growth. The research area is limited by companies that achieved high-speed growth by improving their competitiveness and not as a result of market extension. There are a vast majority of studies that search for determinants of companies' competitiveness (description is presented in the overview article "P. Mohnen and B.H. Hall. Innovation and Productivity: an Update / Eurasian Business Review, 3(1), 2013, 47-65"). Most of them indicates that implementation of different types of innovations (product, process, marketing and organizational) are important for firm's growth. I would like to present the results of econometric and statistical analyses of internal and external factors that influence on company's growth rate. There is strong evidence that emergence of high growth companies (gazelles) is more likely in regions that are famous for their innovativeness. It is an external factor which could be called "appropriate environment for high growth firms". Statistical analyses of regional data demonstrates existence of correlation (coefficient of correlation exceeds 0.5) between the number of high-growth companies and such indicators as "The number of researchers per 10 000 people" (k = 0.59), "The ratio of number of PCT applications to the economically active population" (k = 0.56), "The share of employees with higher education in the total number of population in economically active age" (k = 0.55) and "The ratio of the number of applications for inventions submitted to the Russian Patent Bureau by national applicants, to the economically active population" (k = 0.52). The next step of analysis was to examine intramural factors that determine companies' growth rates. We used closed data collected via national survey of high growth innovative companies ("Rating-TechUp" that was completed in 2013 year - http://www.ratingtechup.ru/en/rate/). Econometric analysis provided evidence that the mains intramural factor that determine company's growth rates are share of new (innovative) production in the company's overall sales and expenditures on education of company's staff. Determined external and intramural factors could be used for elaborating recommendations for implementation of industrial policy in Russia.
Keywords: 330; high-growth companies; gazelles; innovative regions; determinants of competitiveness